Cardiovascular disease event rates in patients with severe psoriasis treated with systemic anti‐inflammatory drugs: a Danish real‐world cohort study. (11th October 2012) - Ahlehoff, O.; Skov, L.; Gislason, G.; Lindhardsen, J.; Kristensen, S. L.; Iversen, L.; Lasthein, S.; Gniadecki, R.; Dam, T. N.; Torp‐Pedersen, C.; Hansen, P. R.
Abstract Objectives Psoriasis is a chronic inflammatory disorder associated with cardiovascular morbidity and mortality. Systemic anti‐inflammatory drugs, including biological agents, are widely used in the treatment of patients with moderate to severe psoriasis and may attenuate the risk of cardiovascular disease events. We therefore examined the rate of cardiovascular disease events in patients with severe psoriasis treated with systemic anti‐inflammatory drugs. Design, setting and participants Individual‐level linkage of nationwide administrative databases was used to assess the event rates associated with use of biological agents, methotrexate or other therapies, including retinoids, cyclosporine and phototherapy, in Denmark from 2007 to 2009. Main outcome measure Death, myocardial infarction and stroke. Results A total of 2400 patients with severe psoriasis, including 693 patients treated with biological agents and 799 treated with methotrexate, were identified. Incidence rates per 1000 patient‐years and 95% confidence intervals (CIs) for the composite endpoint were 6.0 (95% CI 2.7–13.4), 17.3 (95% CI 12.3–24.3) and 44.5 (95% CI 34.6–57.0) for patients treated with biological agents, methotrexate and other therapies, respectively. Age‐ and sex‐adjusted hazard ratios (HRs) were 0.28 (95% CI 0.12–0.64) and 0.65 (95% CI 0.42–1.00) for patients treated with biological agents and methotrexate, respectively, using other therapies as the reference cohort. Corresponding HRs for a secondary composite endpoint of cardiovascular death, myocardial infarction and stroke were 0.48 (95% CI 0.17–1.38) and 0.50 (95% CI 0.26–0.97). Conclusion In this nationwide study of patients with severe psoriasis, systemic anti‐inflammatory treatment with biological agents or methotrexate was associated with lower cardiovascular disease event rates compared to patients treated with other anti‐psoriatic therapies.